Na+ mobility in sodium strontium silicate fast ion conductors. Issue 96 (12th October 2015) - Peet, Joseph R.; Widdifield, Cory M.; Apperley, David C.; Hodgkinson, Paul; Johnson, Mark R.; Evans, Ivana Radosavljević
Abstract : Variable temperature 23 Na solid state NMR spectroscopy and spin-lattice relaxation measurements provide the first direct evidence of Na-ion mobility in sodium strontium silicate fast ion conductors. Abstract : We present the first direct evidence of Na-ion mobility in sodium strontium silicate fast ion conductors, based on variable temperature 23 Na solid state NMR spectroscopy and spin-lattice relaxation measurements.